2005
DOI: 10.1177/1066480704270099
|View full text |Cite
|
Sign up to set email alerts
|

The Sandwich Generation: Challenges and Coping Strategies of Multigenerational Families

Abstract: This article presents a review of recent literature of the "sandwich generation" with an emphasis on women. Counseling interventions, family counseling implications, and two case studies follow the literature review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(76 citation statements)
references
References 10 publications
(26 reference statements)
3
58
0
2
Order By: Relevance
“…Furthermore, sex may influence some of the hypothesized relationships. For example, some researchers have suggested that dual-earner men work more hours per week than dual-earner women (Levine and Pittinsky, 1997), and that women are more likely to experience the care-giving responsibilities associated with both child-and elder-care (i.e., the "sandwich generation;" Riley and Bowen, 2005).…”
Section: Limitations and Future Studiesmentioning
confidence: 99%
“…Furthermore, sex may influence some of the hypothesized relationships. For example, some researchers have suggested that dual-earner men work more hours per week than dual-earner women (Levine and Pittinsky, 1997), and that women are more likely to experience the care-giving responsibilities associated with both child-and elder-care (i.e., the "sandwich generation;" Riley and Bowen, 2005).…”
Section: Limitations and Future Studiesmentioning
confidence: 99%
“…Being "stuck" in the middle is a common experience of adult children who have to care for their older parents while tending to their young children (Riley and Bowen, 2005). In the present study, it appears that some adult children solved this conflict by delegating the duty of being physically present to the migrant home care worker.…”
Section: Discussionmentioning
confidence: 84%
“…First, MGCs report experiencing contradiction within their relationships with their care recipients, which is unsurprising given the level of stress described by MGCs (e.g., Charlesworth, 2006;Neufeld et al, 2008;Riley & Bowen, 2005). MGC's reports of A-C's and O-C's influence on relationship satisfaction illustrate dialectic contradictions' fluctuation and multi-vocality.…”
Section: Theoretical Implicationsmentioning
confidence: 94%